Humanitas of the judges, guilt of the accused in some Ciceronian orations? - Mollea, Simone (Ciceroniana On Line, 2022)
At Off. 2, 51, Cicero invokes humanitas to argue that even guilty defendants must have their day in court. Looking back over Cicero’s forensic career from the perspective of On duties, we see that he had made explicit appeal to the judges’ humanitas in 5 speeches (Pro Cluentio, Pro Balbo, Pro Archia, Pro Sulla and Pro Caelio). In light of this, modern scholarship broadly agrees that Cicero may have had little in the way of substantive material to argue in defence of his clients and likely these clients were guilty. This paper does not aim to support this point, that in 44 BCE Cicero was revealing that his past appeals to the judges’ humanitas had been due to the defendants’ guilt. The focus of this paper is to explore how and why in these five speeches, humanitas is used as a device to bring together or divide the judges and other parties to the matter. The argument highlights the extent to which humanitas is an effective rhetorical tool: it distracts judges from the trial itself by flattering them with ennobling comparisons (with Pompey, a great? poet, Cicero himself) and/or by separating them off from outcasts (Oppianicus, Sassia) or from the accusers (Manlius Torquatus, Herennius).